Closed-loop control of product properties in metal forming - Allwood, JM; Duncan, SR; Cao, J; Groche, P; Hirt, G; Kinsey, B; Kuboki, T; Liewald, M; Sterzing, A; Tekkaya, A (Elsevier, 2016)
Metal forming processes operate in conditions of uncertainty due to parameter variation and imperfect understanding. This uncertainty leads to a degradation of product properties from customer specifications, which can be reduced by the use of closed-loop control. A framework of analysis is presented for understanding closed-loop control in metal forming, allowing an assessment of current and future developments in actuators, sensors and models. This leads to a survey of current and emerging applications across a broad spectrum of metal forming processes, and a discussion of likely developments.